2022
DOI: 10.1186/s12872-022-02618-5
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between lipoprotein(a) elevations and the risk of recurrent cardiovascular events in CAD patients with different LDL-C levels

Abstract: Background Lipoprotein(a) [Lp(a)] elevation is an important risk factor for coronary artery disease (CAD). However, the correlation between Lp(a) elevations and the risk of recurrent cardiovascular events in patients with established cardiovascular disease is controversial. Some studies have shown that Low-density lipoprotein cholesterol (LDL-C) levels may influence the association between Lp(a) and cardiovascular risk. Our study aims to explore the correlation between Lp(a) elevations and card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
1
13
0
1
Order By: Relevance
“…In order to improve risk stratification in patients, efforts have been made to develop prognostic predictive tools or risk scores to identify CTO before CAG [ 4 ]. Although some previous studies have analyzed potential predictors related to the high incidence rate of CAD and established a relevant model for CAD in patients before CAG, no research has attempted to conduct a rigorous analysis of the CTO data contained within clinical features as a means to produce more personalized CTO risk assessments [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve risk stratification in patients, efforts have been made to develop prognostic predictive tools or risk scores to identify CTO before CAG [ 4 ]. Although some previous studies have analyzed potential predictors related to the high incidence rate of CAD and established a relevant model for CAD in patients before CAG, no research has attempted to conduct a rigorous analysis of the CTO data contained within clinical features as a means to produce more personalized CTO risk assessments [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated strong associations of Lp(a) and AIP with CAC. 7 8 9 10 11 12 However, several studies have shown a weakened association between Lp(a) and ASCVD risk in patients without high LDL-C. 15 16 29 30 Therefore, whether a consistent association exists between Lp(a) and CAC is questionable in patients without high LDL-C. In the present study, Lp(a) did not predict CACS ≥400 and CAC ≥90th percentile whereas, AIP independently predicted both CAC >0 and CAC ≥90th percentile.…”
Section: Discussionmentioning
confidence: 99%
“…The biological evidence underlying to this association is not yet fully understood. However, Zhu et al 30 presented the following suggestions. Patients with very low LDL-C levels tend to have high levels of activity of LDL receptors and a strong metabolic capacity for Lp(a).…”
Section: Discussionmentioning
confidence: 99%
“…25 , 26 Recent studies showed that vascular disease recurrence in patients with high levels of Lp(a) (≥50 mg/dL) is attenuated only at very low LDL-C (<55 mg/dL) but not when LDL levels ≥70 mg/dL. 27 , 28 Kinetic studies suggest a preferential accumulation of Lp(a) particles in vessel walls which may increase the artherogenic potential of Lp(a) cholesterol over LDL-C. High levels of Lp(a) are highly correlated with rapid progression of coronary atherosclerosis, a strong predictor of adverse outcome. Patients with high Lp(a) levels develop high risk unstable plaques with complex morphology which are prone to rupture.…”
Section: Discussionmentioning
confidence: 99%